2016
DOI: 10.1371/journal.pone.0153715
|View full text |Cite
|
Sign up to set email alerts
|

Friendships and Family Support Reduce Subsequent Depressive Symptoms in At-Risk Adolescents

Abstract: BackgroundEarly life stress (ELS) consists of child family adversities (CFA: negative experiences that happened within the family environment) and/or peer bullying. ELS plays an important role in the development of adolescent depressive symptoms and clinical disorders. Identifying factors that may reduce depressive symptoms in adolescents with ELS may have important public mental health implications.MethodsWe used structural equation modelling and examined the impact of adolescent friendships and/or family sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
160
3
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(201 citation statements)
references
References 79 publications
31
160
3
7
Order By: Relevance
“…The CFQ was developed from a semi‐structured interview based on ethological principles of social relationships and the developmental significance of friendships (Pellegrini & Bartini, 2000). The CFQ has demonstrated good reliability and validity (α = .70, further details available from first author), and has demonstrated ecological validity across two samples (van Harmelen et al., 2016, 2017). The CFA yields a single total score with higher scores indicating more positive perceptions of peer relationships (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CFQ was developed from a semi‐structured interview based on ethological principles of social relationships and the developmental significance of friendships (Pellegrini & Bartini, 2000). The CFQ has demonstrated good reliability and validity (α = .70, further details available from first author), and has demonstrated ecological validity across two samples (van Harmelen et al., 2016, 2017). The CFA yields a single total score with higher scores indicating more positive perceptions of peer relationships (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Childhood family adversity is robustly associated with a range of deviant outcomes including subsequent conduct and emotional disorders, drug misuse, and mental illness (Dunn et al., 2011; Fergusson, Boden, & Horwood, 2008; van Harmelen et al., 2016). As higher prevalence of NSSI is associated with almost all mental illnesses (Dunn et al., 2011; Nock & Kessler, 2006), NSSI may not be a direct response or consequence of CFA itself but arise from subsequent mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent friendships and family support are important protective factors after early life stress (Rutter, 1985, van Harmelen et al 2016. Recently, we showed that adolescent family support reduces later depressive symptoms after differential levels of childhood family adversity, whereas adolescent friendship support reduced later depressive symptoms after childhood family adversity and/or peer victimisation (van Harmelen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, individuals with comparable experiences may not appraise their experiences in the same way (Rutter, 1985(Rutter, , 2012. For instance, perceived levels of threat, rather than actual threat, determine later stress reactivity (van Wingen et al 2011). Therefore, including self-reported appraisal of childhood family experiences may contribute to a more valid and quantifiable measure of adolescent resilient functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation